From Breakouts to Breakthroughs: Homeopathy for Maskne (Homoeopathy for All, 2024)
During the COVID-19 pandemic,  wearing masks became one of the  most effective measures to curb the  spread of the virus. Masks protect  both the wearer and those around  them by filtering out harmful  respiratory droplets, which can carry  viruses. As a simple yet powerful  tool, masks not only helped prevent  the transmission of COVID-19  but also raised awareness of their  broader benefits in reducing the  spread of other infectious diseases  and improving overall public health.  But wearing masks for extended  periods can contribute to various  skin problems, including acne,  irritation, and rashes. To minimize  mask-related acne, it's important  to keep face and mask clean, use  breathable fabrics, and maintain  a proper skincare routine. Along  with this, Homeopathy can play a  major role in managing maskne by  addressing the underlying causes  of skin imbalance and promoting  natural healing.
Keywords: Homoeopathy; Maskne